2019
DOI: 10.1007/s00167-019-05814-7
|View full text |Cite
|
Sign up to set email alerts
|

The unicompartmental knee is the preferred side in individuals with both a unicompartmental and total knee arthroplasty

Abstract: Purpose To determine the preferred knee in patients with both one total and one unicompartmental knee arthroplasty. Method Patients simply with a unicompartmental (UKA) and total knee arthroplasty (TKA) on contralateral sides were retrospectively screened from three senior knee surgeon's logs over a 15 year period. Patients safe and free from other diseases to affect gait were approached. A total of 16 patients (mean age 70 ± 8) agreed to ground reaction force testing on an instrumented treadmill at a fair pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
0
16
1
Order By: Relevance
“… 47 - 51 Clinically, data suggest that walking on a slope with a TKA in situ is functionally more difficult than post-UKA. 7 However, in this study, no differences were detected over this range of flexion. Differences in slope walking may be a consequence of other factors, such as loss of proprioception following resection of the cruciate ligaments, rather than differences in extensor function.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“… 47 - 51 Clinically, data suggest that walking on a slope with a TKA in situ is functionally more difficult than post-UKA. 7 However, in this study, no differences were detected over this range of flexion. Differences in slope walking may be a consequence of other factors, such as loss of proprioception following resection of the cruciate ligaments, rather than differences in extensor function.…”
Section: Discussioncontrasting
confidence: 66%
“…More than 1.5 million total knee arthroplasty (TKA) procedures are performed annually worldwide 1 to treat end-stage osteoarthritis (OA) in one, two, or three knee compartments. 2 - 5 While many patients benefit from TKA, for some, poor postoperative function can lead to disability, especially on stairs or when walking on slopes, 6 , 7 and patient dissatisfaction rates of up to 25% have been reported. 8 - 11 Consequently, there has been much recent debate in the orthopaedic community regarding how to improve knee function and patient satisfaction following arthroplasty.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current operative treatment modalities of advanced osteoarthritis are total knee arthroplasty (TKA) and unicompartmental knee arthroplasty (UKA). However, replacing all the affected and nonaffected surfaces is considered the gold standard procedure [ 2 , 3 ]. On the other hand, many surgeons argue the superiority of UKA in unicompartmental cases to spare the undamaged compartments, despite having higher revision rates when compared to TKA [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that patients with a UKA and a contralateral TKA tend to favour the UKA, which maintains a more natural gait. 16 - 18 UKA also offers faster recovery, less postoperative pain, and lower rates of thromboembolism, cerebrovascular events and 30-day mortality, compared with TKA. 19 …”
Section: Introductionmentioning
confidence: 99%